2005
DOI: 10.1093/ptj/85.8.755
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic Analyses of Global Synkinesis in the Paretic Upper Limb After Stroke

Abstract: Background and Purpose. Global synkinesis (GS), or motor irradiation, is an involuntary movement associated with the coactivation of numerous muscles in one limb when the opposite limb is active. The electromyographic (EMG) patterns of people with stroke and people who were healthy were analyzed to characterize GS development in relation to joint involvement and to attempt to relate these findings to clinical observations. Subjects and Methods. Twenty patients with stroke, divided into 2 groups with either gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 37 publications
0
28
1
2
Order By: Relevance
“…Moreover, those stroke survivors with better motor recovery and control analogs demonstrated a more marked directional effect on overflow amplitude than the stroke survivors with poorer recovery. A previous study reported that the amount of motor overflow decreased progressively with involvement of more distal joints (18), but this patterned organization of MO was not seen in the stroke survivors with poor recovery. Together with gradient-change in MO with joint involvement (18), insufficient directional effect on MO found in this study seems to be another physiological watershed in the stroke recovery process.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Moreover, those stroke survivors with better motor recovery and control analogs demonstrated a more marked directional effect on overflow amplitude than the stroke survivors with poorer recovery. A previous study reported that the amount of motor overflow decreased progressively with involvement of more distal joints (18), but this patterned organization of MO was not seen in the stroke survivors with poor recovery. Together with gradient-change in MO with joint involvement (18), insufficient directional effect on MO found in this study seems to be another physiological watershed in the stroke recovery process.…”
Section: Discussionmentioning
confidence: 77%
“…A previous study reported that the amount of motor overflow decreased progressively with involvement of more distal joints (18), but this patterned organization of MO was not seen in the stroke survivors with poor recovery. Together with gradient-change in MO with joint involvement (18), insufficient directional effect on MO found in this study seems to be another physiological watershed in the stroke recovery process. Although physiological mechanisms underlying the directional effect is not completely clear, it probably pertains to usagedependent decline in transcallosal inhibition commonly found in professional musicians with intensive practices for years (29,30).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Auchdas Auftretenv on Synkinesien ist entgegender in derBobath-Therapie vertre-tenenL ehrmeinung für denW iedererwerb motorischer Fertigkeitenn icht ungünstig, sondern geht mitverbessertenfunktionellen Fertigkeiteneinher (24).…”
Section: Thema Nervenheilkunde3/2006unclassified
“…In patients with central nervous system lesions, abnormal synergistic coactivations have been mostly measured during isolated contractions in static conditions [ 10 - 12 ]. In such tasks, where constraints due to movement are reduced and where the central nervous system has fewer parameters to control, the relationship between the coupling of the torques generated across the joints and the pattern of muscular recruitment is more easily interpreted than in dynamic tasks [ 11 ].…”
Section: Introductionmentioning
confidence: 99%